I am unable to understand the equation viz., X + P = 2(B + P + Q).
the stem says 'In P years he will be twice older than Bob will be Q years later.', then the equation should be X + P = 2(B + Q).
How could you get from the stem that P years is after B+Q years?
Could you explain me? It may be problem with my English. However, do explain me. Has anybody else got the same equation?
15. Kenny is three times older than Bob. In P years he will be twice older than Bob will be Q years later. Which of the following represents Kennyâ€™s age comparing to Bobâ€™s? (If X = Kennyâ€™s age)
(a) X + P = 6X(P+Q).
(b) 2(X+P) = 3X + Q.
(c) (X+P)/2 = X/3 + P + Q.
(d) 3(X+P+Q) = 2X.
(e) 3X = 2(P + Q).
Thnx & Rgds,